Zeitschrift für romanische Philologie (De Gruyter, 1877)
The journal Zeitschrift für romanische Philologie (ZrP), founded by Gustav Gröber in 1877, covers the entire field of Romance linguistics as well as medieval literature and textual criticism. The journal publishes four issues annually. The publication languages are French, Spanish, Portuguese, Italian and Romanian as well as German and English.